Pengaruh Aplikasi PGPR (Plant Growth Promoting Rhizobacteria) dan Air Leri terhadap Pertumbuhan Bibit Kelapa Sawit di Pre Nursery - Galih Valerianifo; Hangger Gahara Mawandha; Elizabeth Nanik Kristalisasi (Program Studi Agroteknologi INSTIPER, 2023)
Pre-nursery is one of the important stages in preparing oil palm planting materials. PGPR (Plant Growth Promoting Rhizobacteria) are beneficial bacteria for plants that colonize around plant roots. Leri water is one of the by-products of household activities that contain beneficial properties for plants. This study aims to determine the application of PGPR and air leri on the growth of oil palm seedlings in pre-nursery and to determine the interaction between the application of PGPR and air leri on the growth of oil palm seedlings in the pre-nursery. This research was conducted from February to July to October 2022 in Maguwoharjo Village, Sleman, Yogyakarta. The study used an experimental method which was arranged in a completely randomized design (CRD) consisting of two factors. The first factor is the PGPR application, which consists of four levels, namely 0 ml, 10 ml, 20 ml, and 30 ml. The second factor is the application of leri water consisting of three levels, namely every 2 days, 4 days, and 6 days. Observations were analyzed using variance at the 5% level of significance. If there is a significant difference then proceed with Duncan's multiple range test at the 5% level of significance. The results showed that there was an interaction between the application of PGPR and leri water on seedling height, stem diameter, number of leaves, root length, root volume, and shoot fresh weight, crown dry weight, root dry weight, plant fresh weight, and plant dry weight. Whereas in the application of PGPR and leri water to root fresh weight there was no interaction and each treatment was not significantly different.